Molecular Relatedness of Salmonella enterica Typhimurium Isolates from Feces and an Infected Surgical Wound [Corrigendum] - Qin H; Guo Y; Li Y; Zheng R (Infection and Drug Resistance, 2020)
Qin H, Guo Y, Li Y, Zheng R. Infect Drug Resist. 2020;13:2139—2144. The authors have advised affiliation 4 on page 2139 is incorrect. The correct affiliation should read “4Department of Clinical Laboratory, the Affiliated Hospital of Kunming University of Science and Technology, Kunming, Yunnan, People’s Republic of China”. The authors apologize for this error. Read the original article